Older adults' perspectives on primary care telemedicine during the COVID‐19 pandemic. Issue 12 (28th September 2022) - Bhatia, Roma; Gilliam, Elizabeth; Aliberti, Gianna; Pinheiro, Adlin; Karamourtopoulos, Maria; Davis, Roger B.; DesRochers, Laura; Schonberg, Mara A.
Abstract: Background: Prior to the COVID‐19 pandemic there were many barriers to telemedicine primary care for adults ≥65 years including insurance coverage restrictions and having lower digital access and literacy. With the pandemic, insurance coverage broadened and many older adults utilized telemedicine creating an opportunity to learn from their experiences to inform future policy. Methods: Between April 2020 and June 2021, we conducted a cross‐sectional multimethod study of English‐speaking, cognitively‐intact, adults ≥65, who had a phone‐only and/or video telemedicine visit with their primary care physician within one large Massachusetts health system (10 different practices) since March 2020. The study questionnaire asked participants their overall satisfaction with telemedicine (7‐point scale) and to compare telemedicine with in‐person care. We used linear regression to examine the association between participants' demographics, Charlson comorbidity score, and survey completion date with their satisfaction score. The questionnaire also included open‐ended questions on perceptions of telemedicine; which were analyzed using qualitative methods. Results: Of 278 eligible patients reached, 208 completed the questionnaire; mean age was 74.4 years (±4.4), 61.5% were female, 91.4% were non‐Hispanic White, 64.4% had ≥1 comorbidity, and 47.2% had a phone‐only visit. Regardless of their age, participants reported being satisfied with telemedicine; median score was 6.0 on the 7‐point scale (25th percentile = 5.0 and 75th percentile = 7.0). Non‐Whites satisfaction scores were on average 1 point lower than those of non‐Hispanic Whites ( p = 0.02). Those with comorbidity reported scores that on average were 0.5 points lower than those without comorbidity ( p = 0.07). Overall, 39.5% felt their telemedicine visit was worse than in‐person care; 4.9% thought it was better. Participants appreciated telemedicine's convenience but described frustrating technical challenges. While participants preferred in‐person care, most wanted telemedicine to remain available. Conclusions: Adults ≥65 reported being satisfied with primary care telemedicine during the pandemic's first 14 months and wanted telemedicine to remain available. Abstract : See related Editorial by Biese et al . in this issue.